2005
DOI: 10.1111/j.1528-1167.2005.33504.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for the Surgery for Mesial Temporal Lobe Epilepsy: Longitudinal Analysis

Abstract: Summary:Purpose: Determining long-term prognostic factors of surgery for mesial temporal lobe epilepsy (MTLE) is important for identifying ideal candidates and predicting the prognosis for individual patients. We tried to identify the prognostic factors of anterior temporal lobectomy (ATL) for MTLE with longitudinal multivariate analysis.Methods: Two hundred twenty-seven patients with MTLE were included in this study. The primary outcome variable was patient status 1-5 years after surgery: seizure free, or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
98
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 26 publications
8
98
2
5
Order By: Relevance
“…13,15,16,24,29,34) Children operated on after 6 years of age had no better outcome than children operated on in infancy or at preschool age. 15) Younger age at surgery is a significant and independent predictor and an independent prognostic factor of good surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15,16,24,29,34) Children operated on after 6 years of age had no better outcome than children operated on in infancy or at preschool age. 15) Younger age at surgery is a significant and independent predictor and an independent prognostic factor of good surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…15) Younger age at surgery is a significant and independent predictor and an independent prognostic factor of good surgical outcome. 13) Longer preoperative illness predicts poorer outcome 34) or late recurrence. 25) The duration of preoperative epilepsy is not a reliable predictor of final surgical outcome among patients with medial temporal sclerosis, 18,19) whereas the duration of epilepsy is inversely and significantly correlated with seizure outcome among patients with extratemporal epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have observed that a longer epilepsy duration before surgical treatment predicted worse seizure outcome 19,22 . However, Baldauf et al did not reach those conclusions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al 19 and Junna et al 20 observed that a younger age at surgery was predictive of a favorable postsurgical outcome. Additionally, Sirven et al 21 studied a large number of patients undergoing temporal lobectomy and observed that patients younger than 50 years had a higher likelihood of seizure freedom compared with those older than 50 years, although the procedure was considered safe and beneficial in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation